2017
DOI: 10.18632/oncotarget.19557
|View full text |Cite
|
Sign up to set email alerts
|

cFLIP critically modulates apoptotic resistance in epithelial-to-mesenchymal transition

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Our findings support these observations, as ML327 induces epithelial-like features and sensitizes ES cells to TRAIL-mediated apoptosis. We have previously reported the capacity of ML327 to mediate TRAIL sensitization in colon cancer cells, demonstrating this process to be in part mediated by down regulation of cFLIPs [18]. Our results are in support of our previous investigation, as we observe consistent downregulation of cFLIPs in association with ML327-mediated TRAIL sensitization.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings support these observations, as ML327 induces epithelial-like features and sensitizes ES cells to TRAIL-mediated apoptosis. We have previously reported the capacity of ML327 to mediate TRAIL sensitization in colon cancer cells, demonstrating this process to be in part mediated by down regulation of cFLIPs [18]. Our results are in support of our previous investigation, as we observe consistent downregulation of cFLIPs in association with ML327-mediated TRAIL sensitization.…”
Section: Discussionsupporting
confidence: 92%
“…ML327 has previously been shown to reduce cFLIPs expression in colon cancer cell lines, thereby sensitizing them to TRAIL-induced apoptosis [18]. We therefore analyzed the response of cFLIPs to ML327 treatment in 3 ES cell lines and found that cFLIPs protein was reduced (Figs.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In TRAIL-sensitive and RPM-EP melanoma cells expressing DR5, TRAIL-mediated apoptosis inhibition was observed; due to the expression of cFLIP, TRAIL-R1 negative melanoma cells could not undergo apoptosis induced by TRAIL [ 44 ] . A study on epithelial-mesenchymal transition (EMT) showed that high expression of cFLIPs in the exogenous region caused resistance to apoptosis triggered by TRAIL, and deletion of cFLIPs was sufficient to overcome TRAIL resistance in carcinoma cell lines; when ML327 (an isoxazole-based small chemical) was induced into an immortalized mouse mammary epithelial cell line, there was a partial reversal of TGF-β-induced EMT [ 45 ] .…”
Section: Trail and Cancer Therapymentioning
confidence: 99%
“…Because EMT leads to the dysregulation and disassembly of this E-cadherin–TRAIL complex, cancer cells with a mesenchymal phenotype increase their protection against TRAIL-induced apoptosis. 81 However, in patients with early-detected colorectal cancer, DR4 and DR5 can be expressed in parallel with E-cadherin, but their co-localisation at the membrane is not systematic. 82 Moreover, the potential interactions between the death receptors (including the decoy receptors known as death receptor competitors that lack the intracellular death domain responsible for the propagation of TRAIL-induced apoptotic signal) and cadherins remains unanswered, despite the potential mechanistic impact these cell processes hold.…”
Section: Death Receptor-mediated Features Of Emtmentioning
confidence: 99%